TUJUH KONTAK KONSELING MENYUSUI SEBAGAI UPAYA MENCEGAH TERJADINYA POSTPARTUM BLUES - Yanik Muyassyaroh; Aulia Fatmayanti; Anjar Astuti; Kuswanto Kuswanto (Jurnal Abdi Masyarakat, 2019)
Postpartum blues is the onset of mental disorders in mothers postpartum, which in turn can adversely affect the mother and the baby. One of the factors triggering postpartum the difficulty breastfeeding which can increase the risk of depression. 7 contacts lactation counseling done from the beginning that since the mother's womb 28 weeks old after birth is not expected to happen later breastfeeding difficulties that can lead to postpartum blues. This has encouraged the devotees to carry out the Community Service (Pengabmas) dissemination of research results in the form of seven contacts influence on the incidence of postpartum lactation counseling blues at the Village Karangjati City District Blora Blora. Service to the community is intended to provide education to pregnant women in order to prepare for the postpartum period to be able to provide exclusive breastfeeding to reduce the risk of postpartum blues. Community service activities are carried out at 7 meetings in PKD Karangjati using methods lectures, discussion, and demonstration. This activity begins with the pre-test and post-test ends with the result is increased knowledge after being given counseling with a lecture and demonstration. The conclusion form the community service is an increased knowledge of pregnant women about the benefits of seven contacts lactation counseling can reduce the risk of postpartum blues.